Content Cytotoxicity Studies of Colorectal Carcinoma Cells Using Printed Impedance Sensors - Anis Nurashikin Nordin; Irmanisha Ibrahim; Ahmad Fairuzabadi Mohd Mansor; Yumi Zuhanis Has-Yun Hashim; Ioana Voiculescu (Institute of Advanced Engineering and Science, 2017)
Monitoring the effectiveness of drugs on cancer cells is crucial for chemotherapeutics studies. In-vitro cell-based biosensors can be used as an alternative for characteristic studies of cells’ response to drugs. Cell-based sensors provide real-time measurements and require smaller sample volumes compared to conventional T-flask measurement methods. This paper presents a biosensor that detects in real-time, impedance variations of human colon cancer, HCT-116 cells when treated with anti-cancer agent, 5-Fluorouracil (5-FU). Two different extracellular matrix (ECM); polyaniline and gelatin were tested and evaluated in terms of attachment quality. Polyaniline was found to provide the best attachment for HCT-116 cells and was used for cytotoxicity studies. Cytokinetic behavior indicated that 5-FU inhibited HCT-116 cells at IC50 of 6.8 µg/ mL. Trypan blue exclusion method for testing cell viability was used to validate the impedance measurements, where the cancer cell concentrations were reduced to 35% when treated with 2.5 µg/mL, and 50% when treated with 6.8 µg/mL. The results generated by the microfabricated impedance biosensor are comparable to the Trypan blue method since both gave similar cell growth trend. It can be concluded that the impedance biosensor has potential to be used as an alternative method in drug testing applications.Monitoring the effectiveness of drugs on cancer cells is crucial for chemotherapeutics studies. Invitrocell-based biosensors can be used as an alternative for characteristic studies of cells’ response todrugs. Cell-based sensors provide real-time measurements and require smaller sample volumescompared to conventional T-flask measurement methods. This paper presents a biosensor that detects inreal-time, impedance variations of human colon cancer, HCT-116 cells when treated with anti-canceragent, 5-Fluorouracil (5-FU). Two different extracellular matrix (ECM); polyaniline and gelatin were testedand evaluated in terms of attachment quality. Polyaniline was found to provide the best attachment forHCT-116 cells and was used for cytotoxicity studies. Cytokinetic behavior indicated that 5-FU inhibitedHCT-116 cells at IC50 of 6.8 μg/mL. Trypan blue exclusion method for testing cell viability was used tovalidate the impedance measurements, where the cancer cell concentrations were reduced to 35% whentreated with 2.5 μg/mL, and 50% when treated with 6.8 μg/mL. The results generated by themicrofabricated impedance biosensor are comparable to the Trypan blue method since both gave similarcell growth trend. It can be concluded that the impedance biosensor has potential to be used as analternative method in drug testing applications.